Organic tourism as a tool to raise healthy tourism destinations: an investigation in Turkey - Uğurlu , Kaplan (Applied Studies in Agribusiness and Commerce, 2014)
The aim of the paper is to specify the items that effect the importance of organic tourism both for human life and sustainable tourism destinations. The fundamental point of the study is to focus on organic farming both as a tool for welfare of the destinations and their importance and potential for the upcoming future of healthy generations using the data collected from segments of the society such as administrators, non-governmental organization members and farmers. The study is also based on an extensive secondary research analyzing the diverse literature regarding the organic/ecological/sustainable/destination tourism. The results are supplemented by semi-structured interviews. To date, many people have been interested in visiting villages and having an experience in living farms. This tourism activity is combined with facilities to create potent economic force to small villages. Besides, consuming organic food is one of the most important attitudes to live healthier and longer by being or working in the farms or villages as a visitor which creates a new era in tourism named as organic tourism. Organic tourism primarily targets tourists, tours organized for the purpose of health, relaxation activities, agriculture education, culture and gastronomy. The research offers a practical help for farmers, local governors, local people (especially villagers), tour operators and visitors fleeing from the intensity of city life in the light of the findings.